1976
DOI: 10.1017/s0022112076000773
|View full text |Cite
|
Sign up to set email alerts
|

Pressure and force distributions on a sharp-nosed circular cylinder at large angles of inclination to a uniform subsonic stream

Abstract: This paper reports an experimental investigation of pressure and force distributions on a sharp-nosed circular cylinder inclined to a uniform low-speed air flow under conditions of laminar separation of the boundary layer. The main concern is with the out-of-plane force (i.e. the side force if the body is at incidence). The experimental model consisted of an extensively pressure-tapped cylinder to which four different noses were fitted. The results show that there is an oscillatory distribution of out-of-plane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
1

Year Published

1980
1980
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(45 citation statements)
references
References 3 publications
(4 reference statements)
0
44
0
1
Order By: Relevance
“…Lamont and Hunt [32], Dexter and Hunt [33] were among the first to propose some influence factors which may lead to the repeatability problem for wind tunnel test results. The first factor: Lamont and Hunt [32] found that the freestream turbulence of wind tunnels may cause the switching of the asymmetric vortex into their mirror image states if the turbulence level is large enough, resulting in the repeatability problem. Therefore they proposed that this kind of experimental test should be carried out in a low turbulence wind tunnel.…”
Section: Flow Phenomena and The Problemsmentioning
confidence: 98%
See 2 more Smart Citations
“…Lamont and Hunt [32], Dexter and Hunt [33] were among the first to propose some influence factors which may lead to the repeatability problem for wind tunnel test results. The first factor: Lamont and Hunt [32] found that the freestream turbulence of wind tunnels may cause the switching of the asymmetric vortex into their mirror image states if the turbulence level is large enough, resulting in the repeatability problem. Therefore they proposed that this kind of experimental test should be carried out in a low turbulence wind tunnel.…”
Section: Flow Phenomena and The Problemsmentioning
confidence: 98%
“…As mentioned above, the roll angle effect on the asymmetric vortex flow over slender bodies has been studied extensively by many scholars [18,[29][30][31][32][33][34][35]. The research group [18,29,[32][33][34] leaded by Hunt was among the earliest to work on this flow phenomenon.…”
Section: Behaviors Of Asymmetric Vortex Flow With Roll Anglesmentioning
confidence: 99%
See 1 more Smart Citation
“…Different means are used to reduce asymmetries or to remove them: e.g., roughness on the pointed body surface can be used (Lamont and Hunt 1976;Ericsson and Reding 1981;Modi et al 1984); blunting near the nose, or adding modifying elements (such as strakes, helical trips, nose booms .... ) are worthy solutions (Modi et al 1984;Stahl 1990;Rao 1977;Coe et al 1972;Sarpkaya 1966). Finally, the lateral forces and moments can be suppressed by blowing near the nose (Cornish and Jenkins 1978;Skow and Peake 1982;Mourtos and Roberts 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Previous experimental investigations of the flow behind a missile at high angle of attack have shown that the asymmetric vortex wake and resulting side force is sensitive to roll angle and tunnel turbulence level (1)(2)(3)(4). In addition, it is known that for some angles of attack, the vortices may be bi-stable; the asymmetric vortex structure may suddenly switch from one stable state to another (3)(4)(5).…”
mentioning
confidence: 99%